The role of social media in shaping purchasing decisions in Phnom Penh, Cambodia - Simeng Ly; Hong Soun (Faculty of Business and Economics, University of Surabaya, 2026)
The rapid evolution of social media has transformed consumer behavior, making it a critical tool for influencing purchasing decisions in the digital age. This study, titled